2020
DOI: 10.3390/su12219129
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Applying Open Educational Practices in Higher Education during COVID-19: Impacts on Learning Motivation and Perceptions

Abstract: Open Educational Resources (OER) have been researched for a long time in the open education field. Researchers are now shifting their focus from resources to practices for delivering open education, an area called Open Educational Practices (OEP). However, there is little information in the related literature regarding the design of an OEP-based course or the impact of these types of courses. Therefore, this study designs a new OEP-based course at a public university for teaching family education during the CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 28 publications
0
20
1
2
Order By: Relevance
“…Generally, public sharing and open licensing were optional. There were two studies in which it was explicitly required (Bonica, 2018;Zhang et al, 2020). In the Bonica (2018) study, students had the option of using a pseudonym rather than their names if there were concerns about privacy.…”
Section: Rq1: Open Pedagogy Definitions/explanationsmentioning
confidence: 99%
“…Generally, public sharing and open licensing were optional. There were two studies in which it was explicitly required (Bonica, 2018;Zhang et al, 2020). In the Bonica (2018) study, students had the option of using a pseudonym rather than their names if there were concerns about privacy.…”
Section: Rq1: Open Pedagogy Definitions/explanationsmentioning
confidence: 99%
“…The impact of COVID-19 on the educational processes that used to take place prior to the COVID-19 pandemic has been significant. Researchers worldwide documented the huge impact school closures had on students' achievement during the first months of the pandemic [1][2][3]. During this first period, online learning emerged as the main solution as many families had to be confined [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as well as efforts to increase the awareness of OEP, more training should be provided to help teachers acquire the OEP competencies that are needed to design their OEP-based courses. Zhang et al [37], for instance, designed an OEP-based course for teaching family education and reported that specific training had to be provided for teachers to enhance their skills in (1) being effective facilitators of the learning process while using an OEP-based course and (2) designing diversified engaging learning activities that match the needs of all learners (e.g., shy learners).…”
Section: Discussionmentioning
confidence: 99%